Gradient-band-gap strategy for efficient solid-state PbS quantum-dot sensitized solar cells. Issue 17 (15th April 2019) - Ma, Chengfeng; Shi, Chengwu; Lv, Kai; Ying, Chao; Fan, Shasha; Yang, Yang
Abstract : Solid-state gradient-band-gap PbS QDSCs achieved a PCE of 6.29% under 1 sun and 7.21% under 0.5 sun. Abstract : To improve charge separation and enhance open-circuit voltage ( V oc ) in solid-state quantum-dot sensitized solar cells (QDSCs), gradient-band-gap PbS quantum-dots were first and easily constructed by two-step spin-coating the Pb(NO3 )2 solution and the mixed solution of Na2 S and 1, 2-ethanedithiol via successive ionic layer absorption and reaction (SILAR). The fabricated solid-state gradient-band-gap PbS QDSCs exhibited a V oc of 0.70 V, a short-circuit photocurrent density ( J sc ) of 9.65 mA·cm −2, a fill factor (FF) of 0.60, and a photoelectric conversion efficiency (PCE) of 4.08%, while the inverse gradient-band-gap PbS QDSCs showed a V oc of 0.59 V, a J sc of 5.86 mA·cm −2, an FF of 0.49 and a PCE of 1.69%. By optimization, the best solid-state gradient-band-gap PbS QDSCs achieved a V oc of 0.65 V and a PCE of 6.29% under 1 sun, and a V oc of 0.60 V and a PCE of 7.21% under 0.5 sun. The V oc of 0.65 V was relatively high, and the PCE of 6.29% was the highest value among solid-state QDSCs constructed using SILAR.